2013
DOI: 10.1371/journal.ppat.1003295
|View full text |Cite
|
Sign up to set email alerts
|

The JAK-STAT Transcriptional Regulator, STAT-5, Activates the ATM DNA Damage Pathway to Induce HPV 31 Genome Amplification upon Epithelial Differentiation

Abstract: High-risk human papillomavirus (HPV) must evade innate immune surveillance to establish persistent infections and to amplify viral genomes upon differentiation. Members of the JAK-STAT family are important regulators of the innate immune response and HPV proteins downregulate expression of STAT-1 to allow for stable maintenance of viral episomes. STAT-5 is another member of this pathway that modulates the inflammatory response and plays an important role in controlling cell cycle progression in response to cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 45 publications
2
112
0
1
Order By: Relevance
“…How HPV activates ATM is currently unclear, though we have found that E7 expression alone is sufficient to induce activation of ATM targets (12), possibly through the induction of replication stress and DNA damage (14,15). Recent studies by Hong and Laimins demonstrated that E7-induced STAT5 activation is necessary for ATM activation, possibly through peroxisome proliferator-activated receptor ␥ (PPAR␥) expression (16). We, as well as others, have shown that expression of viral helicase E1 can also stimulate ATM activation (8,17).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…How HPV activates ATM is currently unclear, though we have found that E7 expression alone is sufficient to induce activation of ATM targets (12), possibly through the induction of replication stress and DNA damage (14,15). Recent studies by Hong and Laimins demonstrated that E7-induced STAT5 activation is necessary for ATM activation, possibly through peroxisome proliferator-activated receptor ␥ (PPAR␥) expression (16). We, as well as others, have shown that expression of viral helicase E1 can also stimulate ATM activation (8,17).…”
mentioning
confidence: 65%
“…The DNA repair protein 53BP1, which is expressed at high levels in HPV-positive cells (18), has also been shown to be a mediator of ATM function (89,90), with its effects on ATM activity enhanced in situations in which the MRN complex is present at low levels (90). Activated STAT5 has been shown to be necessary for ATM activation in HPV-positive cells (16), though whether this occurs in an MRN-dependent manner is unclear. Regardless, the maintenance of ATM signaling upon differentiation is not sufficient to drive productive viral replication, as the decreased levels of Nbs1 still act as a barrier to viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism for the repression of transcription by E2 due to steric hindrance is based on the location of E2BS adjacent the TATA box, effectively blocking the binding of the TATA-binding protein (TBP) (Steger & Corbach, 1997). proposed to be essential for replication during vegetative amplification (Hong & Laimins, 2013). Topoisomerase II binding protein (TopBP1) and Breast Cancer 1 (BRCA1) were both found to interact with E2 and directly influence transcription/replication Kim, Lee, Gwan Hwang, Hwang, & Choe, 2003).…”
Section: E2mentioning
confidence: 99%
“…E7 is proposed to activate STAT5 phosphorylation which causes the activation of the ATM pathway (Hong & Laimins, 2013). E6 and E7 were found to independently activate caspases in differentiating cells (Moody, Fradet-Turcotte, Archambault, & Laimins, 2007).…”
Section: Papillomavirus Replicative Programmentioning
confidence: 99%
“…In HPV-31, E7 was shown to activate STAT5 directly and E6 was not required (22). However, different HPV types are known to differ in the strategies employed to achieve the same state (24)(25)(26).…”
mentioning
confidence: 99%